EVALUATION OF POSSUM SCORING SYSTEM IN SURGICAL DECISION MAKING AND AUDITS: Evaluation of Possum Scoring System - Malik, Maj Momin; Shukr, Irfan (Pakistan Armed Forces Medical Journal, 2010)
Objectives: To test the validity of POSSUM scoring system as a surgical decision-making and audit tool by determining the association between actual deaths and POSSUM Score predictions in a sample population of patients undergoing abdominal surgical procedures.Study Design: Descriptive study.Place And Duration of Study: Combined Military Hospital, Rawalpindi, Pakistan from October 2007 to November 2008.Patients and Methods: POSSUM score was calculated prospectively for all patients admitted to Surgical Ward I, CMH Rawalpindi, and scheduled to undergo laparotomy. Patients with previous history of surgery and day- surgery cases were excluded. Patients were stratified into three risk groups based on POSSUM Score, and 30 patients were picked randomly for the purpose of this study. The difference between observed deaths and the three risk groups was analysed for statistical significance by means of chi square test.A total of 90 patients were included in the study. All were males and above 12 years of age, with mean age 34. A significant association was observed between POSSUM Score and actual deaths (P